Epidemiology, antigenic and genetic characterization of animal rabies cases in Pará state, Brazilian Amazon (Research, Society and Development, 2022)
Antigenic and genetic characterization of Rabies lyssavirus (RABV) variants isolated in the Rabies Diagnostic Laboratory of Instituto Evandro Chagas (Ananindeua, Pará, Brazil), as well as verifying the geographic distribution of positive samples, according to the mesoregions of the state, from samples from the state of Pará received in the period 2010 to 2017. Positive samples were antigenically characterized by the monoclonal antibody panel (MAb) provided by the Centers for Disease Control and Prevention (CDC) and when there was no compatibility with the MAb panel, the samples were genetically characterized according to the Barbosa methodology and collaborators. The 73 positive samples were submitted to antigenic characterization, of which 72.60% were compatible with some reading pattern of the MAb panel; 63.01% were compatible with AgV 3; 9.59% were compatible with AgV 2 and 27.40% did not match any reading pattern and were forwarded to genetic sequencing. All 20 samples submitted to partial N gene sequencing were grouped into the AgV 3 group, with a bootstrap value of 99%. In the state of Pará, a change in the epidemiological cycle of rabies was observed, therefore, the AgV 3, associated with the hematophagous bat Desmodus rotundus, was widely identified. These data differ from those found in other decades, in which AgV 2 was predominant, this change is possibly a result of mass vaccination campaigns. It was also possible to observe that the temporal distribution of rabies in the state suggests possible failures in disease control and prevention actions.